DETERMINAN SOSIAL DAN DEMOGRAFI TERHADAP KEJADIAN STRES PADA PEKERJA DKI JAKARTA TAHUN 2023 - ADELLA DELISA PUTRI (2024)
Stress can be interpreted as an individual's psychological, physiological and behavioral response to stressors. Social and demographic determinants are factors that cause stress. This research aims to determine the factors that contribute to the incidence of stress in DKI Jakarta workers. This research is a quantitative study using a cross-sectional design. The analysis used is linear regression on a total population of 200 workers. The instruments in this study used the Perceived Stress Scale (PSS-10), Multidimensional Scale of Perceived Social Support (MSPSS), social capital, UCLA loneliness, and Social Network Index (SNI) questionnaires. The results showed that social determinants (social support and social capital) and demographic factors (age, work income, distance traveled). The correlation value between the five dominant indicators and stress was 0.5040 (50.4%). The conclusion is that the variables of social support, social capital, age, work income and distance traveled contribute to stress.